A 3D RITSS approach for total stress and coupled-flow large deformation problems using ABAQUS. (July 2018) - Ullah, Shah Neyamat; Hou, Lee Fook; Satchithananthan, Umashankaran; Chen, Zongrui; Gu, Hai
Abstract: A large deformation finite element (LDFE) method is implemented in a commercially available finite element software in three dimensions using a re-meshing and interpolation technique. The method allows fully coupled pore fluid effective stress analysis as well as decoupled total stress analysis to be performed. The method is described step by step following its application to offshore pipeline penetration analysis in full 3D. The results indicate versatility of the approach, showing reasonable agreement with existing solutions.